Dynamics of antioxidant properties, phenolic compounds, and transcriptional expression of key enzymes for the phenylpropanoid pathway in leaves of field‐grown winter wheat with different nitrogen fertilization schemes. Issue 3 (6th March 2019) - Stumpf, Beate; Yan, Feng; Wen, Gaiping; Eder, Klaus; Honermeier, Bernd
Abstract: Wheat is a field crop with high relevance for food production worldwide. An adequate supply with nitrogen (N) is crucial for the grain yield and grain quality of wheat. However, little is known about the influence of N fertilization on phenolic compounds, such as phenolic acids and flavonoids, in the leaves of wheat ( Triticum aestivum L. ssp. aestivum cv. Genius) under field conditions. Therefore, a field experiment was set up with winter wheat grown under different N fertilization regimes to investigate the influence of N supply on antioxidant properties in general as well as on distinct phenolic acids and flavonoids in the leaves of wheat plants. In the present study, total phenolic concentration and antioxidant capacity were negatively influenced by higher dosages of N fertilizer. Antioxidant properties were mainly determined by chlorogenic acid and homoorientin, a phenolic acid and a flavonoid, respectively. The production of these phenolic compounds was not limited by the gene transcription of phenylalanine ammonia lyase or cinnamate 4‐hydroxylse, the key enzymes of the phenylpropanoid pathway, since the transcription of these enzymes was not significantly influenced by N fertilization.